Pengaruh Dana Simpanan Wadiah Terhadap Bonus Wadiah Pada Bank Syariah Indonesia Periode 2021-2024 - Rahma Sari Zein; Srisudiarti; Anggraini, Tuti (JOM, 2025)
This study was conducted to examine the effect of wadiah savings funds on wadiah bonuses at PT Bank Syariah Indonesia. Wadiah bonuses are an important issue in Islamic banking as they represent a form of reward given to customers for their deposits, which can influence customers' decisions in choosing Islamic banking products. In this context, a better understanding of the factors affecting wadiah bonuses is crucial to enhancing the appeal of Islamic banking products and retaining customers. The variable "wadiah savings funds" is defined as the total deposits collected from customers in the form of wadiah savings, while "wadiah bonuses" are measured as the rewards given to customers based on their wadiah savings balances. The data for this study were obtained from the official website of Bank Syariah Indonesia. The method used in this study is multiple linear regression analysis, with hypothesis testing performed using t-statistics to examine the coefficients simultaneously at a 5% significance level. The analysis results show that the t-test for the variables of wadiah savings and wadiah demand deposits has a positive and significant effect on wadiah bonuses. Simultaneously, wadiah savings funds also have a positive and significant effect on wadiah bonuses. The adjusted R-squared value of the model is 0.424690, indicating that the independent variables explain 42.47% of the variation in wadiah bonuses, while the remaining percentage is influenced by other factors not included in this study. Thus, this study provides valuable insights for the development of Islamic banking products and more effective marketing strategies.